Struttura e localizzazione dei gruppi di imprese in Emilia Romagna - Roberto Bianchi; Maria Sole Brioschi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
– This paper aims at investigating the presence and the main features of business groups in Emilia Romagna. The research is based on a sample comprising about 48 thousand firms and about 540 thousand employees from Emilia Romagna, the latter representing more than 42 per cent of the total regional employment. First, we find that the presence of corporate grouping in Emilia Romagna is comparable to that documented at national level. Moreover, and surprisingly enough, we show that the extension of the group organizational form is significant also in industrial districts, suggesting that ownership linkages among firms do play a role and should not be neglected in the analysis of these production systems. Although the analysis requires some further investigation, these results support the view that also in Emilia-Romagna the actual size of firms is larger and the number of owners is lower than official statistics reveal. This result has important economic policy implications, as the industrial policy of Emilia-Romagna has traditionally been oriented to supporting small and very small firms.
Keywords: 330